Analytic optical design of linear Fresnel collectors with variable widths and shifts of mirrors. (March 2015) - Abbas, R.; Martínez-Val, J.M.
Abstract: Linear Fresnel collectors still present a large margin to improve efficiency. Solar fields of this kind installed until current time, both prototypes and commercial plants, are designed with widths and shifts of mirrors that are constant across the solar field. However, the physical processes that limit the width of the mirrors depend on their relative locations to the receiver; the same applies to shading and blocking effects, that oblige to have a minimum shift between mirrors. In this work such phenomena are studied analytically in order to obtain a coherent design, able to improve the efficiency with no increase in cost. A ray tracing simulation along one year has been carried out for a given design, obtaining a moderate increase in radiation collecting efficiency in comparison to conventional designs. Moreover, this analytic theory can guide future designs aiming at fully optimizing linear Fresnel collectors' performance. Highlights: Errors due to off-axis aberration and to beam aperture depend on the mirror location. Design of mirrors with sun reference increase the maximum flux intensity. Shading and blocking errors vary across the solar field if constant shift design is used. A design with variable shift of mirrors drives to an increase of efficiency.